Análise da pressão nos processos de escrita manual: uma revisão sistemática - Santos, Matheus Moralles dos (Universidade Estadual Paulista (Unesp), 2022)
The aim of the study was to carry out a systematic review on the pressure of handwriting in schoolchildren. Research strategy: research guided by PRISMA recommendations. The guiding question was elaborated based on the PICO strategy, being: is the pressure variable considered to influence the quality of handwriting in schoolchildren with and without dysgraphia? The selected descriptors were: pressure, handwriting, anticipatory movement, dysgraphia, and their synonyms, in Portuguese and English. Studies indexed in the following databases were identified: Pubmed/MEDLINE, BIREME and SciELO. Selection criteria: articles directed to the topic published in Portuguese and English were selected, without distinction of period and the research carried out between the dates 10/21/2021 and 10/27/2021. Data analysis: The data collected through the identification (I) and selection (II) stages were analyzed in the eligibility stage (III). Results: From the rigorous reading of the 28 studies chosen for full reading in the inclusion stage (IV), thirteen articles were classified as containing the necessary answers to the research question. Conclusion: The results allowed it to be concluded that pressure was an influencing variable for the quality of handwriting.

O objetivo do estudo foi de realizar uma revisão sistemática sobre a pressão da escrita manual em escolares. Estratégia de pesquisa: pesquisa norteada pelas recomendações do PRISMA. A pergunta norteadora foi elaborada com base na estratégia PICO, sendo: a variável pressão é considerada influenciadora da qualidade de escrita manual em escolares com e sem disgrafia? Os descritores selecionados foram: pressão, escrita manual, movimento antecipatório, disgrafia, e seus sinônimos, nos idiomas português, inglês. Foram identificados estudos indexados nas bases dados: Pubmed/MEDLINE, BIREME e SciELO. Critérios de seleção: foram selecionados artigos direcionados ao tema publicados nos idiomas português e inglês, sem distinção de período e a pesquisa realizada entre as datas 21/10/2021 e 27/10/2021. Análise dos dados: Os dados levantados por meio das etapas de identificação (I) e seleção (II), foram analisados na etapa da elegibilidade (III). Resultados: A partir da leitura rigorosa dos 28 estudos elegidos para a leitura na íntegra na etapa de inclusão (IV), treze artigos foram classificados como contendo as respostas necessárias à pergunta de pesquisa. Conclusão: Os resultados permitiram concluir que a pressão foi uma variável influenciadora para a qualidade da escrita manual.
Analysis of pressure in handwriting processes: a systematic review
Keywords: Pressure; Handwriting; Dysgraphia; Pressão; Escrita manual; Disgrafia